Hepatocellular adenoma. About a case. - Zeoli, Mariana; Guillén, Alison; Delgado, Juan; Andreoli, Gustavo; Valiñas, Roberto (Cirugía del Uruguay, 2024)
Hepatocellular adenoma (HA) is a benign liver tumor, its diagnosis has advanced thanks to advances in molecular methods, which facilitated its division into subtypes, with different prognoses and therapeutic indications. We present the clinical case of a 40-year-old patient with an ultrasound finding of a liver tumor, a voluminous heterogeneous solid lesion on a CT scan of the abdomen and pelvis, compatible with a steatotic adenoma on MRI (associated with HNF1 alpha mutation). Surgical treatment was decided, with resection of segments 6 and 7. The pathology concluded in short: Compatible with the inflammatory subtype. Hepatic adenomas (HA) are rare, solitary, benign epithelial tumors. They occur in women of childbearing age and associated with the consumption of oral contraceptives and estrogens. These tumors predominate in the right liver, with proliferation of cells similar to normal hepatocytes, but disorganized and without normal lobular architecture, without bile ducts or supporting connective tissue. HA, as well as the rest of the benign liver tumors, have increased their incidence in the hand with the advancement of abdominal imaging. The importance of differentiation with the rest of the benign liver tumors arises from the malignant potential of these. We can classify patients according to the molecular profile associated with immunohistochemical markers. Imaging studies are fundamental for tumor differentiation in diagnosis and therapeutic planning. The treatment will be individualized, determined by the clinic, the variety of subtypes, and the evolution. Due to the complexity of the disease, the treatment of AH is one of the best examples of an individualized approach in hepatobiliary units.